DIMENSI PRAGMATISME POLITIK DALAM BINGKAI NEGARA DEMOKRASI - Satryo Pringgo Sejati; Ahmad Burhan Hakim (The Republic : Journal of Constitutional Law, 2023)
Democracy is a political system and ideologue that has been widely applied in various countries in the post-cold war world. Democracy tries to become an international political regime that is so gallant and ideal in terms of the system and the dimensions of its use. Democracy does not only discuss matters of state and government, but also issues of basic human values ​​in the form of human rights, humanity, egalitarianism, gender, femininity and even capitalist economic issues which are also closely related to democracy. But another fact occurred, the ideal dimension of democracy shifted to pragmatism and transactional politics with the emergence of the reality of the rampant practice of money politics in Indonesia. The emergence of these things is certainly not in a vacuum and without effort. The issue of money politics has become a big and terrible scourge amid the consolidation and development of democracy in Indonesia today. Political pragmatism occurs not only at the central level in the form of presidential elections but has reached the grass roots, namely elections to villages. So that this is suspected by many parties as part of the emergence of a culture of corruption in Indonesia. In other words, the rampant cases of corruption that occur in Indonesia are more likely to occur because of the extraordinarily large cost politics in the implementation of democracy. Both in terms of subject and political object in Indonesia. So this will become a political pathology that must be addressed immediately. The political pragmatism that occurs in Indonesia has an extraordinary transactional political economy dimension. So this should be a red note for democracy in Indonesia. So the ideals of reform that have been echoed since 1998 can be realized gradually. However, if the problem of money politics is still rife, then the ideals of reform in the form of realizing Indonesia as a democratic country will experience extraordinary distortions.